Les dynamiques raciales de la production de Michael Jackson (1979-2001) : aspects commerciaux, musicaux et visuels - Isabelle Stegner-Petitjean (Transatlantica)
Our article analyses Michael Jackson’s artistic production, through marketing, stylistic and visual aspects, targeting racial dynamics and tensions which invigorate its narrative layers. The first part is about the colorist charts, the ubiquitous posture of Jacksonian opuses and the way they invigorated the notion of crossover. The second part analyzes the stylistic eclecticism of Jackson’s pop music and the way he uses the conventions from musical and racial categorization. Finally, the third part is about the racial dynamics and tensions carried both by some of his visual productions and the way he negotiated his own fluid corporality.